Biochemical Bone Markers During the Transition Period Are Not Influenced by Parenteral Treatment With a High Dose of Cholecalciferol but Can Predict Milk Fever in Dairy Cows - Starič, Jože; Hodnik, Jaka Jakob (Frontiers in Veterinary Science, 2021)
Despite being studied extensively, there are still many knowledge gaps in milk fever prevention and it is still a prevalent disease. Various interventions have been used in its prevention; however, none has proven to be entirely effective. The study aimed to assess the effectiveness of high dose vitamin D3 parenteral supplementation and the mechanism of its action by studying blood minerals and biochemical bone markers. Further, we assessed the potential of biochemical bone markers, measured in the close-up dry period, as predictors of clinical milk fever after calving. The study was conducted on 56 high yielding dairy cows, before their 4th or higher lactation. They were divided into three groups based on season (summer, winter) and supplementation (vitamin D). Cows (n=13) were parenterally supplemented with 10 million IU of vitamin D3 (DUPHAFRAL® D3) 10 - 2 day before calving. Blood samples were collected one month and ten to two days before calving, and 0-48 hours and 10-20 days after calving. The samples were analysed for blood minerals, bone specific alkaline phosphatase (bALP) and C-terminal telopeptide of type I collagen (CTx), alkaline phosphatase and estradiol. In this study high dose vitamin D3 supplementation did not statistically reduced the incidence of milk fever. The use of biochemical bone markers in the close-up dry period to predict clinical milk fever was limited to the winter (housed) group. The area under the curve for bALP was AUC = 0.804 and AUC = 0.846 for CTx using ROC analysis. The bALP curve had the best ratio at the cut-off point 13.85 U/L with the sensitivity at 90% and specificity 64.3%. While CTx had the ratio of 90% sensitivity and 78.6% specificity at the cut-off point 0.149 ng/mL. Close-up dry dairy cows with CTx ≥0.121 ng/mL had a 3.8 times higher chance of succumbing to milk fever. We were unable to prove that high dose vitamin D3 parenteral supplementation is a viable technique for milk fever prevention, as it did not alter bone metabolism. Biochemical bone markers are a promising tool for predicting milk fever incidence; however, further studies are needed to confirm their clinical use.